2021
DOI: 10.3947/ic.2021.0029
|View full text |Cite
|
Sign up to set email alerts
|

Which Group Should be Vaccinated First?: A Systematic Review

Abstract: Background Since the supply of coronavirus disease 2019 (COVID-19) vaccines will be limited worldwide, it is essential to prioritize vaccination based on scientific evidence. Although several frameworks and studies on vaccine distribution have been published, no published systematic review has evaluated the prioritization of the COVID-19 vaccine. Materials and Methods We searched 4 different databases, PubMed, SCOPUS, Web of Science, and EMBASE for articles published be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 23 publications
1
22
1
Order By: Relevance
“…Certain relatively small differences between occupational groups may be explained by the prioritization of access to vaccination for these groups, because they generally have a higher epidemiological risk of acquiring the disease through more frequent and closer contact with others [ 20 , 21 ]. The occupational groups analyzed in our study enjoy high prestige in the society, also expressed by their ethical standards [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Certain relatively small differences between occupational groups may be explained by the prioritization of access to vaccination for these groups, because they generally have a higher epidemiological risk of acquiring the disease through more frequent and closer contact with others [ 20 , 21 ]. The occupational groups analyzed in our study enjoy high prestige in the society, also expressed by their ethical standards [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since HCWs form the frontline combat force against COVID-19, and therefore fall in the high-risk group, several nations have included them in the high priority group as part of their first phase of vaccination programs [ 8 ]. Not only are they at increased risk of becoming infected themselves, but also of onward transmission to colleagues, hospital attendees, family members, etc.…”
Section: Introductionmentioning
confidence: 99%
“…However, the best strategies and dosing intervals to provide maximum benefit, especially in the context of the new variants spread, still need to be clearly defined [ 63 ]. Similarly, although many policies define priority groups to administer vaccines as reported in our results, a systematic review concluded that the current evidence on prioritization is still insufficient and there is need of adequately powered research assessing this issue [ 65 , 66 ].…”
Section: Discussionmentioning
confidence: 90%